A tunable gelatin-hyaluronan dialdehyde/methacryloyl gelatin interpenetrating polymer network hydrogel for additive tissue manufacturing. (1st July 2022) - Anand, Resmi; Salar Amoli, Mehdi; Huysecom, An-Sofie; Amorim, Paulo Alexandre; Agten, Hannah; Geris, Liesbet; Bloemen, Veerle
Abstract: Methacryloyl gelatin (GelMA) is a versatile material for bioprinting because of its tunable physical properties and inherent bioactivity. Bioprinting of GelMA is often met with challenges such as lower viscosity of GelMA inks due to higher methacryloyl substitution and longer physical gelation time at room temperature. In this study, a tunable interpenetrating polymer network (IPN) hydrogel was prepared from gelatin-hyaluronan dialdehyde (Gel-HDA) Schiff's polymer, and 100% methacrylamide substituted GelMA for biofabrication through extrusion based bioprinting. Temperature sweep rheology measurements show a higher sol-gel transition temperature for IPN (30 °C) compared to gold standard GelMA (27 °C). Furthermore, to determine the tunability of the IPN hydrogel, several IPN samples were prepared by combining different ratios of Gel-HDA and GelMA achieving a compressive modulus ranging from 20.6 ± 2.48 KPa to 116.7 ± 14.80 KPa. Our results showed that the mechanical properties and printability at room temperature could be tuned by adjusting the ratios of GelMA and Gel-HDA. To evaluate cell response to the material, MC3T3-E1 mouse pre-osteoblast cells were embedded in hydrogels and 3D-printed, demonstrating excellent cell viability and proliferation after 10 d of 3D in vitro culture, making the IPN an interesting bioink for the fabrication of 3D constructs for tissue engineering applications.